Model atomistic protrusions favouring the ordering and retention of water - Pandey, Prithvi Raj; Roy, Sudip (Physical Chemistry Chemical Physics, 2014)
The ordering of water molecules near model linear atomistic protrusions is studied using classical molecular dynamics simulations. The protrusions are made up of Lennard-Jones particles of hydrophobic and hydrophilic blocks. Simulations are performed at a range of temperatures and pressures, keeping the position of the protrusions fixed. At different temperatures and pressures, the ordering and residence time of water molecules is enhanced on the surface of the hydrophilic block. Detailed analysis of the systems shows that the surface region is potentially the most energetically favorable for water molecules, which is consistent with the tetrahedral ordering of water molecules. A competition between energetics and structuring is observed from residence time calculations.